Development of weed competitive rice variety under water deficit conditions through marker-assisted backcross breeding - Ab Jalil, Masitah (2018)
Weed is one of the most troublesome pests in rice cultivation especially in water deficit areas, where farmers are commonly used herbicides to control it. Hence, it is important to develop rice variety that has capability to withstand water deficit and higher weed interference conditions, using an environmentally friendly method, such as marker-assisted backcross breeding. Eight rice varieties viz. AERON1, MR185, MR211, MR219, MR232, MR253, MR263 and MRQ74 were evaluated for their performances in water and weed stress conditions. From this study, two varieties (AERON1 and MRQ74) with the best performances were selected as donor and recurrent parental plants, respectively, for molecular breeding study. In molecular study, two foreground and 57 background markers were found as suitable to be used along the breeding study. The foreground markers were RM242 and RM263, which are linked markers to root length genes for drought tolerance. MRQ74 and AERON1 were crossed and backcrossed to generate F1, BC1F1 and BC2F1 populations, respectively. Rice lines of BC2F1 population were self-pollinated to produce BC2F2 population. Chi-square (χ2) analysis for BC1F1 and BC2F1 populations showed good fit to the expected segregation ratio (1:1) for a single dominant gene model (d.f.=1, P>0.05) in Mendelian law for both foreground markers. The Chi-square (χ2) values for RM242 and RM263 were χ2=3.1 and χ2=0.03, and χ2=1.01 and χ2=0.22, in BC1F1 and BC2F1 populations, respectively. In each BC1F1 and BC2F1 populations respectively, 18 and 25 rice lines were revealed as to carry both foreground markers. The highest RPG percentage for BC1F1 and BC2F1 populations were found in line (L) 50-39 with 71.4% and L45-6-24 with 90.8%, respectively. In BC2F2 population, the Chi-square (χ2) values for RM242 and RM263 were χ2=2.81 and χ2=2.97, respectively, and showed good fit to the expected marker segregation ratio (1:2:1) for a single dominant gene model (d.f.=2, P>0.05) in Mendelian law. The highest RPG percentage was discovered in L45-6-24-23 with 93.0%. BC2F2 population had also been evaluated for its agro-morphological traits and tolerance to water deficit conditions by using several drought indices, rank and standard deviation of rank method. Through BC2F2 population, 12 rice lines viz. L45-27-3-7, L50-39-8-5, L50- 39-8-8, L45-27-10-18, L45-27-10-28, L45-27-8-13, L45-27-8-28, L45-27-8-34, L50- 39-7-15, L45-6-24-10, L45-6-24-20 and L45-6-24-23 were found to carry both foreground markers, whereas L2 (L50-39-8) was discovered as the most tolerant line to water deficit conditions in this study. The usage of molecular markers in this study is responsible to accelerate the development of new rice lines that can withstand water deficit conditions and possessed good weed competitive ability.